(untitled) (Foro de Educacion, 2017)
Tunisia is affected by many changes, including the reform of the education system that plays a crucial role. The Ministry of Education together with Trade Unions (UGTT) and the Arab Institute of Human Rights are tracing the outlines of the reform, through an experiment of participatory democracy, synthesized through the preparation of a national report, which is analyzed here. The reform aims to change profoundly the current educational system: programs, manuals, the training of teachers, teaching, all these aspects will be included. Faced with the current economic situation and the problems affecting the country, from the religious extremism to the economic crisis, attempts have been made to examine the solutions proposed by various players involved. After a brief historical reconstruction of the reforms that have affected the Tunisian school system, a current reform is discussed, focusing especially on the school textbooks and on the image of Europe that they carry. Based on the opening to the other, discussed in the manuals, how can one explain the diffusion of religious fanaticism among certain groups of young people? How can the school consolidate the emerging democracy? These are the questions that are tried to be answered, leaving open the possibility of different interpretations.